Foreign aid and the health sector: A case study from Palestinian National Authority - Mataria, Wafa Ahmed (AUC Knowledge Fountain, 2018)
Foreign Aid (FA) is considered a tool for promoting economic and human development. Considerable amounts of FA are directed to Health. The role of FA in development, as well as, in health, has been a subject of debate with inconclusive results on its impact. This study concentrates on FA in the Health Sector in Palestine, in the period following the establishment of the Palestinian National Authority in 1994. A qualitative research approach was used throughout the study to explore, describe and explain the roles, procedures and challenges of FA in the health sector. The research concluded that FA has a positive impact on the health sector outcomes in Palestine. FA contributed to the establishment of institutional structures and capacities within the health sector, as well as, in service provision. Nevertheless, the following challenges still need to be addressed in order to increase FA effectiveness: the Israeli occupation; the continuing influence of donors' agendas; the politicization of aid; the competition between different FA recipients; the low accountability of donors towards recipients; and the miscommunication and inadequate coordination between various actors.